The “Children of Nature” and “Our Province”: The Rev. John Strachan’s Views on the Indigenous People and the Motives Behind the American Invasion of Upper Canada, 1812-1814 - Robertson, James (Ontario History, 2012)
Throughout what came to be known as the War of 1812, The Rev. John Strachan wrote and spoke on a variety of topics related to the conflict. The focus of this article is on his views of the Native peoples and why he believed that Upper Canadians should embrace these “sons of nature” as brothers. It was his argument that the United States desired Upper Canada because it provided a more confined landmass within which they could exterminate the indigenous tribes and free up the West for American expansion. Strachan defended the autonomy of the Natives, the superiority of English governance, and the centrality of Upper Canada in the theatre of war. These writings both challenged the prevalent assumption at the time that Natives were simply pawns in the contest and posited a rarely examined explanation of why Upper Canada was vital to both Native and Imperial concerns.